Understanding Civil Society and Social Institution During The Period of Prophet Muhammad - Lukis Alam (Journal of Social Studies, 2025)
This study examines the intricate dynamics of civil society and social institutions during the transformative period of Prophet Muhammad in the 7th century. Delving into historical narratives, the study aims to unravel the multifaceted dimensions of community life and societal structures that emerged under the guidance of the Prophet. It investigates the role of civil society in fostering social cohesion, ethical values, and mutual support within the nascent Muslim community.Examining the Prophet's teachings, governance, and interpersonal relationships, the research sheds light on the formation and functioning of social institutions during this pivotal era. It scrutinizes the significance of religious principles in shaping civil society and influencing the establishment of social norms. Leveraging historical records, primary sources, and qualitative methods, the study navigates through the rich tapestry of early Islamic society, seeking to unravel patterns, trends, and dynamics that shaped civil structures and social institutions. Moreover, the study investigates the impact of the Prophet's actions on institutionalizing justice, inclusivity, and charity, elucidating their enduring influence on Muslim societies. By understanding civil society and social institutions in the context of Prophet Muhammad's time, the findings aim to contribute not only to historical scholarship but also to contemporary discussions on the role of religion in shaping civil societies and social institutions.